2020
DOI: 10.3390/su12051852
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Dimension of the Employment Market Exposition to Digitalisation—The Case of Austria

Abstract: Digitalisation, referred to as the fourth industrial revolution, is gradually becoming part of all areas of life. The progressing digitalisation inspires new business models, restructures production processes and provides new revenue and value-producing opportunities. Simultaneously jobs are becoming abdicable and livelihoods can get threatened. To analyse the spatial context of the susceptibility of regional labour markets to 4.0 technology in Austria, the occupation-based assessment of digitalisation probabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
(61 reference statements)
0
4
0
1
Order By: Relevance
“…Additionally to the competitiveness factors mentioned above, digitalization has become a critical factor for competitiveness recently. There is a rapid development of ICTs, which pressures enterprises to conduct business within the framework of the Fourth Industrial Revolution (Industry 4.0); with global markets and strong competition, some traditional manufacturing firms are implementing new maintenance innovations and policies, based on digitalization and a data-driven approach [4][5][6]. This further indicates that the application of modern information-communication technologies (ICTs) by enterprises is an important factor in sustainable development.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally to the competitiveness factors mentioned above, digitalization has become a critical factor for competitiveness recently. There is a rapid development of ICTs, which pressures enterprises to conduct business within the framework of the Fourth Industrial Revolution (Industry 4.0); with global markets and strong competition, some traditional manufacturing firms are implementing new maintenance innovations and policies, based on digitalization and a data-driven approach [4][5][6]. This further indicates that the application of modern information-communication technologies (ICTs) by enterprises is an important factor in sustainable development.…”
Section: Introductionmentioning
confidence: 99%
“…As the endowment of resources varies considerably across the geographical environment in China, several scholars have accounted for these geospatial variations while assessing the impact of digital economy on the employment structure. Hat et al (2020) adopted the Austrian case study to report that only a few urban areas and small towns encounter the issue of disappearing jobs, and labor substitutability is relatively higher in rural areas than in urban cities [ 18 ]. Zhang et al (2021) reported that digital economy has promoted the development of China’s industrial structure, and this growth is characterized by regional heterogeneity [ 19 ].…”
Section: Theoretical Analysis and Research Hypothesismentioning
confidence: 99%
“…Данную тенденцию также отмечают K. Hat и G. Stoeglehner, говоря о том, что происходит отказ от рабочих мест и появляется проблема трудоустройства молодежи, не имеющей никакого опыта работы (Hat, Stoeglehner, 2020). Они констатируют, что в Австрии рабочие места в городах в меньшей степени подвержены исчезновению, при том что в муниципалитетах, расположенных в основном в сельской местности, уязвим целый ряд профессий.…”
Section: Introductionunclassified